BATUAN METAMORF KOMPLEKS MELANGE LOK ULO KARANGSAMBUNG - BANJARNEGARA, JAWA TENGAH - PATONAH , ATON
Lok Ulo melange Complex is situated in Karangsambung and Banjarnegara areas, Central Java. This complex is characterized by the occurrence of Tertiary and Pre-Tertiary rocks as fragments embeded in sheared clay matrix. The fragments consist of ophiolite, metamorphic, chert and carbonate rocks. The presence of Lok Ulo melange Complex itself is product of subduction between Indo–Australian and Eurasian plates since Cretaceous age. Grab-sampling on fragments of metamorphic rocks indicate the presence of high grade (glaucophane schist, granulite and gness), medium grade (amphibolite and epidote amphibolite) and low grade (philite, muscovite schist and chlorite epidote schist) metamorphic rocks within the area. The high grade metamorphic rock is represented by glaucophane schist. Glaucophane schist consists of almandine spesartine, salite, ferro salite, augite, ferroaugite, pigeonite; the kind of amphibole are Mg–cataphorite, glaucophane, crossite and hornblende; and quartz. The secondary minerals are albite, chlorite, epidote, tremolite and actinolite. The latter mineral assemblage indicates that the rock was formed at 580o- 500oC and 14,5 – 4 kbar (depth 50 – 14 km). The rocks of medium grade are amphibolite and epidote-amphibolite; Amphibolite schist is dominated by hornblende, garnet, and plagioclase. The secondary mineral is quartz. Amphibolite has retrogration in temperature 550oC - 500oC and pressure 4 – 3 kbar (depth 14 – 10 km). Epidote amphibolite schist consists of garnet, hornblende, plagioclase, quartz, actinolite and epidote. The low grade rocks are muscovite schist and chlorite epidote schist. Mineral assemblage in muscovite schist (the type of plagioclase are albit and oligoklas, muscovite, quartz, almandin spesartin, chorite and epidote) indicates the temperature and pressure of 480oC at the pressure of 6 kbar (depth 21 km). This rock has also retrogration in temperature 290oC and pressure 4 kbar (depth 14 km). Temperature and pressure obtained from the high grade metamorphic rocks (glaucophane schist) are in the lower interval of pressure-temperature for subduction environment. The presence of recrystallization of pyroxene to amphibole and to glaucophane; glaucophane to chlorite; chlorite replacing garnet showed retrogration process; as well as low grade metamorphic rocks such as phyllite, muscovite schist and chlorite epidote schist, represent the retrograde phases in lower temperature-pressure conditions. Data from the metamorphic rocks explain the accretion and exhumation process of high grade metamorphic rocks from subduction depth to the surface condition.